Effect of chemical clarification of oral fluids on the detection of porcine reproductive and respiratory syndrome virus IgG. (September 2018) - Henao-Díaz, Yuly A.; Giménez-Lirola, Luis; Poonsuk, Korakrit; Cheng, Ting-Yu; Wang, Chong; Ji, Ju; Baum, David H.; Main, Rodger G.; Zimmerman, Jeffrey J.
Routine collection and testing of oral fluid (OF) samples facilitates porcine reproductive and respiratory syndrome virus (PRRSV) surveillance in commercial swine herds in a cost-effective, welfare-friendly fashion. However, OFs often contain environmental contaminants that may affect liquid handling and test performance. Traditional processing methods (e.g., filtration or centrifugation) are not compatible with high-throughput testing because of the burden of additional processing costs and time. OF "clarification" using chemical flocculants is an alternative approach not widely explored. Therefore, we evaluated the effect of chitosan-based clarification treatment on a commercial PRRSV OF ELISA. Serum and individual OFs were collected from vaccinated pigs ( n = 17) at −7 to 42 d post-vaccination and subdivided into 4 aliquots. Each aliquot was clarified (treatment A, B, C), with the 4th aliquot serving as untreated control. All samples were tested by PRRSV OF ELISA immediately after treatment and then were held at 4°C to be re-tested at 2, 4, 6, and 14 d post-treatment. Quantitative and qualitative treatment effects were evaluated. A Kruskal–Wallis test found no significant difference in ELISA S/P responses among treatments by days post-treatment. No difference was detected in the proportion of positive PRRSV antibody samples among treatments (Cochran Q, p > 0.05). Treatment of swine OFs using chitosan-based formulations did not affect the performance of a commercial PRRSV OF ELISA. Chitosan (or other flocculants) could improve OF characteristics and could be adapted for use in the field or in high-throughput laboratories.